Form over substance - Jerinić, Jelena (Central European Public Administration Review, 2020)
The article analyses Serbian legislation and case law applicable to electoral disputes, in particular those relevant to the determination of facts in these disputes, and the potential influence of procedural rules on the efficiency of protection of constitutionally guaranteed electoral rights. Besides Serbian legislation and case law, the analysis leans on the relevant European standards, including the case law of the European Court of Human Rights. The results show that in practice, electoral commissions and courts use a limited circle of means of evidence and that the evidence submitted by complainants is not evaluated in the same way as the one coming from electoral boards. Although the application of general rules on administrative disputes is explicitly envisaged in electoral laws, the Administrative Court usually defers to the decisions and reasoning of electoral commissions, without supplementing the facts within court procedure, and relatively rarely or selectively decides in full jurisdiction. The author suggests amendments to the relevant legislation, aiming at a more explicit inclination towards the relevant procedural norms or, possibly, special regulation of evidencing in electoral legislation. In her view, a more explicit direction towards the application of the rules of general administrative procedure, in particular rules on evidencing, would lead to their more consistent application in practice.
Keywords: Administrative Court; administrative procedure; dokazi; elections; electoral rights; evidence; Serbia; Srbija; upravni postopek; upravno sodišče; volilne pravice; volitve